Association of NAD+ levels with metabolic disease in a community-based study - Liu, Yuhe; Chen, Xueyu; Deng, Xuan; Yang, Fan; Zheng, Jinping; Zhou, Tianyun; Xu, Ling; Xie, Xiaomei; Ju, Zhenyu; Wang, Baoguo; Zhang, Caiping; Zhou, Yong (Frontiers in Endocrinology, 2023)
Background: Nicotinamide adenine dinucleotide (NAD+) is a coenzyme and plays a crucial role involved in several metabolic processes. To explore the association of nicotinamide adenine dinucleotide (NAD+) levels with metabolic disease (MD) in adults. Methods: In this cross-sectional study, all data were collected from the Jidong community. The MD was defined as the presence of one or more of the following disease components: hypertension, dyslipidemia, diabetes, hyperuricemia, obesity, and non-alcoholic fatty liver disease (NAFLD). The MD components were categorized into three groups: those with one component, those with two components, and those with three to six components. The whole blood NAD+ level was measured using a cycling assay and LC-MS/MS analysis. The participants were divided into four groups based on their NAD+ level quartiles. Multivariable logistic regression was used to evaluate the association of the whole blood NAD+ levels with MD. Results: Of the 1,394 eligible participants, the average age was 43.2 years, and 74.3% had MD. In the top quartile of NAD+, the prevalence of MD and each of its components (hypertension, hyperlipidemia, diabetes, hyperuricemia, obesity, and NAFLD) were 87.9% 35.2%, 62.3%, 8.7%, 36.9%, 21.0%, 60.5%, respectively. As compared with the lowest NAD+ quartile (≤29.4 μmol/L), the adjusted odds ratios and 95% confidence interval of the highest quartile were 3.01 (1.87-4.87) for MD, 2.48 (1.44-4.29) for 1 MD component, 2.74 (1.45-5.17) for 2 MD components, and 4.30 (2.32-7.98) for 3-6 MD components. The risk of MD began to increase at NAD+ levels of 31.0 μmol/L, as revealed by the gradient associations of NAD+ levels with MD. There was no significant interaction between age, sex, drink, smoke, and NAD+ for MD (p for interaction ≥0.10). Conclusions: Increased NAD+ was significantly associated with MD, as well as its individual components. Our findings provide new evidence for the relationship between blood NAD+ levels and MD.